CAMPUR KODE PADA NOVEL RESIGN! (2018) KARYA ALMIRA BASTARI - Edi Edi; Linggua Sanjaya Usop; Indra Perdana; Elnawati Elnawati; Sudaristi Oktaviani (Universitas Palangka Raya, 2022)
The aims of this research are (1) to describe the form of code mixing in Resign! (2018) by Almira Bastari, (2) describes the function of code mixing in the novel Resign! (2018) by Almira Bastari. The approach used in this research is a qualitative approach. The qualitative approach in this study is to describe the form of code mixing and the function of code mixing. The data analysis technique used in this study is using library techniques and reading and note-taking techniques. The results of this study indicate that there is a code mixing event in the novel Resign! (2018) by Almira Bastari. First, the form of code mixing found in the novel Resign! (2018) by Almira Bastari totaling 251 data. The data specifically relates to the inclusion of elements of English into Indonesian. (1) mixed code in the form of words, there are 143 data, (2) mixed code in the form of phrases, there are 55 data, (3) mixed code in the form of clauses, there are 11 data, (4) mixed code in the form of repetition of words, there are 2 data, (5) mixed code in the form of expressions or idioms, there are 3 data, and (6) code mixing in the form of baster, there are 37 data. Second, the code mixing function contained in the novel Resign! (2018) Almira Bastari's work is (1) to respect the interlocutor there is 1 data, (2) to emphasize a certain intention there are 23 data, (3) to show self-identity there are 30 data, (4) as the influence of the subject matter there are 2 data, (5) as speech opponent specifications there are 192 data, (6) as quotations there are 3 data. As for the code mixing function, the inclusion of English elements into Indonesian as sentence inserts and as repetition was not found by the researchers.